Cover image. (15th July 2020) - Wang, Xiangjian; Yang, Jin; Wei, Changlei; Zhou, Gang; Wu, Lanyan; Gao, Qinghong; He, Xin; Shi, Jiahong; Mei, Yingying; Liu, Ying; Shi, Xueke; Wu, Fanglong; et al.
Abstract : The cover image is based on the Special Issue Article The effect of multisensory illusions on pain and perceived burning sensations in patients with Burning Mouth Syndrome: A proof‐of‐concept study by Amanda H. Phoon Nguyen et al., https://doi.org/10.1111/jop.13065 .